2018
DOI: 10.18295/squmj.2018.18.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Paliperidone Palmitate-Induced Delirium in an Adolescent with Schizophrenia: Case report

Abstract: Schizophrenia is a serious long-term mental disorder which usually presents in adolescence or early adulthood. However, poor adherence to oral antipsychotics can lead to relapse and rehospitalisation. We report an adolescent male with schizophrenia who was referred to the South London & Maudsley National Health Service Foundation Trust, London, UK, in 2015 due to worsening psychotic symptoms. Following poor compliance with oral medications, a four-week regimen of paliperidone palmitate long-acting injections w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…After administration of the 2nd dose of PP, they increased again, and the drug was discontinued (14). Moreover, acute-onset delirium was seen after the second PP dose in an adolescent with schizophrenia (13). In our case, the use of the LAI form of haloperidol was not considered due to transaminitis reported in the literature (20)(21)(22).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…After administration of the 2nd dose of PP, they increased again, and the drug was discontinued (14). Moreover, acute-onset delirium was seen after the second PP dose in an adolescent with schizophrenia (13). In our case, the use of the LAI form of haloperidol was not considered due to transaminitis reported in the literature (20)(21)(22).…”
Section: Discussionmentioning
confidence: 68%
“…Common adverse events with PP use were headache, vomiting, limb pain, and injection site pain (10). Patients with schizophrenia who developed acute persistent circulatory failure and extrapyramidal symptoms requiring vasopressors and mechanical ventilation with death resulting after receiving injections of PP have been reported in the literature (11,12), as have cases with delirium and liver enzyme elevation caused by PP (13,14). In this article, we present a case of high fever and high liver function tests (LFT) immediately after the first dose of PP.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the single case reports, two of them were based on the description of side effects [ 44 , 45 ]. Mirza et al [ 45 ] described a male adolescent inpatient with schizophrenia who developed a severe acute-onset delirium after the second dose of LAI paliperidone (first dose: 150 mg and second: 100 mg).…”
Section: Resultsmentioning
confidence: 99%
“…Looking at the single case reports, two of them were based on the description of side effects [ 44 , 45 ]. Mirza et al [ 45 ] described a male adolescent inpatient with schizophrenia who developed a severe acute-onset delirium after the second dose of LAI paliperidone (first dose: 150 mg and second: 100 mg). The treatment was associated with an improvement of his symptoms, but 10 days after the second dose the patient needed an admission due to fluctuating levels of consciousness and additional symptoms of delirium.…”
Section: Resultsmentioning
confidence: 99%
“…Of related interest, Mirza et al [16] have reported on an adolescent male with schizophrenia. Following poor compliance with oral medications, a 4-week regimen of paliperidone palmitate long-acting injections was initiated, with an initial positive response.…”
Section: Paliperidone Palmitate Long-acting Injectable In Cap Populationmentioning
confidence: 99%